ESRA19-0604 Rescue of LPS-induced left ventricular dysfunction by intralipid is mediated by phosphorylation of stat3. (30th August 2019) - Rahman, S; Makar, C; Matthew, M; Wissa, A; Medzikovic, L; Eghbali, M; Umar, S
Abstract : Background and aims: Intralipid (ILP) has been demonstrated in animal models and humans to mitigate the cardio-depressant effects of local anesthetics and I/R injury, possibly via restoration of metabolic dysfunction, activation of cardio-protective signaling and augmentation of contractility. Methods: 8 adult female SD rats received a single intraperitoneal injection of LPS (20 mg/kg). Echocardiography was performed on the rats at baseline prior to injection of LPS, and then at 6h post-LPS, in order to assess LV ejection fraction. Rats were randomly divided to receive either 20% ILP (n=4) or phosphate buffered saline (PBS; n=4) as a 5 ml/kg bolus followed by a 0.5 ml/kg/min infusion over 10 min and echocardiography was conducted at 1, 5 and 10 min to reassess LVEF. At 10 min, LV tissue was collected and Western blots were performed to assess for GSK and STAT3 phosphorylation. Values are expressed as mean±SEM. P<0.05 is considered statistically significant. Results: Baseline LVEF in PBS and ILP before LPS were 75.7±1.1% and 74.2±1.2%, respectively. 6 h after LPS, LVEF was decreased (LVEF= 54.3±4.8% in PBS, and 46.0±2.5% in ILP; both p<0.05 vs. baseline). Rats treated with ILP had improved EF at 5 min (LVEF=63±3.9% p<0.05 vs.6h post LPS) that peaked at 10 min (LVEF=70.5±2.3%, p<0.05 vs.6h post LPS). PBS group had no significant improvement in LVEF at 5 and 10 min (LVEF=58.4±6.4% and 58.9±7.8%, respectively; both p=ns vs. 6h post LPS). Western blots demonstrated increased phosphorylation of STAT3 (∼2-fold) in ILP treated rats (p<0.05), not GSK phosphorylation. Conclusions: Administration of ILP significantly improves LVF likely mediated via STAT3 phosphorylation.